2003
DOI: 10.1039/b305064e
|View full text |Cite
|
Sign up to set email alerts
|

cis–trans Isomerisation of CpRe(CO)2(H)(ArF) (ArF= C6FnH5−n; n = 0–5) is the rate determining step in C–H activation of fluoroarenes: a DFT study

Abstract: Density functional calculations have been used to examine the reaction of {CpRe(CO) 2 } with fluorobenzenes C 6 F n H 6Ϫn (n = 0-5). Two classes of product have been observed experimentally (using Cp or Cp*): (a) coordination of the arene in an η 2 fashion and (b) C-H activation to form a hydrido-aryl complex. Increasing the number of fluorines on the arene ring was shown to favour C-H activation. The thermodynamic and kinetic (reaction path) aspects of these transformations have been examined with DFT (B3PW91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 60 publications
8
60
0
Order By: Relevance
“…Since the activation occurs at the chlorine ortho with respect to the OMe, then two possibilities for the coordination of the unsaturated fragment [(h 5 -C 5 Me 5 )Re(CO) 2 ] to 2,4,5-trichloroanisole can be envisaged: coordination through the CCl Ä/C(OMe) or CCl Ä/ CH bonds of the molecule. The former can be discarded by considering both experimental results and recent theoretical studies which have demonstrated that the same rhenium fragment coordinate to the less substituted double bond of partially fluorinated [21] and chlorinated [20] benzenes. In the second intermediate, the fragment should coordinate the CCl Ä/CH bond at the 2,3-position of the arene.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Since the activation occurs at the chlorine ortho with respect to the OMe, then two possibilities for the coordination of the unsaturated fragment [(h 5 -C 5 Me 5 )Re(CO) 2 ] to 2,4,5-trichloroanisole can be envisaged: coordination through the CCl Ä/C(OMe) or CCl Ä/ CH bonds of the molecule. The former can be discarded by considering both experimental results and recent theoretical studies which have demonstrated that the same rhenium fragment coordinate to the less substituted double bond of partially fluorinated [21] and chlorinated [20] benzenes. In the second intermediate, the fragment should coordinate the CCl Ä/CH bond at the 2,3-position of the arene.…”
Section: Resultsmentioning
confidence: 93%
“…1) reveals that the activation occurs in the position ortho with respect to the OMe group. Taking into account the model proposed for the C Ã/H and C Ã/F bonds activation of arenes or fluorinated arenes by transition metal complexes [19], and also the experimental evidence for the coordination of chlorobenzenes to rhenium in the complexes (h 5 -C 5 Me 5 )Re(CO) 2 (5,6-h 2 -1,2,4-C 6 H 3 Cl 3 ) and (h 5 -C 5 Me 5 )Re(CO) 2 (5,6-h 2 -1,2,3,4-C 6 H 2 Cl 4 ) [20], we have also considered an intermediate with the chloroarene coordinated in an h 2 -fashion, prior to the insertion of the metal fragment into the C Ã/Cl bond. Since the activation occurs at the chlorine ortho with respect to the OMe, then two possibilities for the coordination of the unsaturated fragment [(h 5 -C 5 Me 5 )Re(CO) 2 ] to 2,4,5-trichloroanisole can be envisaged: coordination through the CCl Ä/C(OMe) or CCl Ä/ CH bonds of the molecule.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, fluorobenzene and 1,2-difluorobenzene lead to isolable complexes coordinated via either one or two fluorines, respectively with d 0 Cp 2 Ti IV , 21 The binding energy to a given fluorobenzene, as calculated in a d 6 cyclopentadienyl rhenium complex with DFT(B3LYP) method, decreases from  2 -HC=CH bond to  2 -HC=CF, and to  2 -FC=CF (discussed in more detail in section 4.2.2.3). 16,88 The preference for coordinating the least fluorinated double bond of fluoroarenes is not general. Ni(PEt 3 ) 2 forms an  2 -complex with C 6 F 5 H which could be detected by NMR spectroscopy, but was fluxional even at the lowest temperatures measured.…”
Section: Energetics Of Coordinationmentioning
confidence: 99%
“…The reactions of niobium imido complexes ( -diketiminate)Nb(=N t Bu)( 6 -C 6 H 6 ) with partially fluorinated benzenes Ar-F yield C-F activation products (-diketiminate)Nb(=N t Bu)(Ar)F. 158 Similarly, TpW(NO)( The mechanism of the C-H activation reaction to form products of type C has been probed by DFT(B3PW91) calculations. 88,100 The Re( 2 -arene) complex is converted to a -C-H complex before oxidative addition occurs to yield a cis product that then isomerizes to the final trans-isomer.…”
Section: Scheme 3 the Five Primary Reactive Channels Describing The mentioning
confidence: 99%
“…However, the selective activation of C-F bonds in the presence of C-H bonds generates additional issues, because many second and third row late transition metal complexes that are capable of the oxidative addition of C-F bonds display lower activation barriers for C-H bond oxidative addition. 4,5 Thus, despite the efficacy of these heavier metals in the activation of perfluorinated aromatic substrates, they are of no utility with more synthetically useful substrates such as penta-, tetra-, tri-and difluorobenzene. Although this difficulty has been bypassed in a few cases by utilizing metal complexes that react with aromatic substrates via electron transfer or nucleophilic mechanisms, 6 these complexes produce activation products which cannot be conveniently incorporated into catalytic cycles.…”
mentioning
confidence: 98%